Damming the Commons : An Empirical Analysis of International Cooperation and Conflict in Dam Location - Olmstead, Sheila M.; Sigman, Hilary (World Bank Group, Washington, DC, 2014)
This paper examines whether countries consider the welfare of other nations when they make water development decisions. The paper estimates econometric models of the location of major dams around the world as a function of the degree of international sharing of rivers. The analysis finds that dams are more prevalent in areas of river basins upstream of foreign countries, supporting the view that countries free ride in exploiting water resources. There is weak evidence that international water management institutions reduce the extent of such free-riding.